Energy Compensation Following a Supervised Exercise Intervention in Women Living With Overweight/Obesity Is Accompanied by an Early and Sustained Decrease in Non-structured Physical Activity - Riou, Marie-Ève; Jomphe-Tremblay, Simon; Lamothe, Gilles; Finlayson, Graham Stuart; Blundell, John Edward; Décarie-Spain, Léa; Gagnon, Jean-Christian; Doucet, Éric (Frontiers in Physiology, 2019)
Background/Objectives Body composition (BC) does not always vary as a function of exercise induced energy expenditure (exercise EE – resting EE). Energy balance variables were measured to understand energy compensation (EC) in response to an exercise intervention performed at low (LOW) or moderate (MOD) intensity. Subjects/Methods Twenty-one women with overweight/obesity (33 ± 5 kg/m2; 29 ± 10 yrs; 31 ± 4 ml O2/kg/min) were randomized to a 3-month LOW or MOD (40 or 60% of VȮ2reserve, respectively) matched to expend 1500 kcal/week (compliance = 97 ± 5%). Body energy stores (DXA), energy intake (EI) (food menu and food diaries), resting EE (indirect calorimetry), total EE (doubly-labeled water), time spent in different activities (accelerometers), appetite (visual analog scale), eating behavior traits and food reward (liking and wanting) were assessed at baseline, after weeks 1 and 2 and at the end of the 3-month exercise intervention. Results EC based on BC changes (fat mass and fat-free mass) was 49 ± 79% and 161 ± 88% in LOW and MOD groups, respectively (p = 0.010). EI did not change significantly during the intervention. However, eating behavior traits and food reward had changed by the end of the 3-month supervised exercise. Non-structured physical activity (NSPA) decreased across the intervention (p < 0.002), independent of the intensity of the exercise training. Conclusion Women with overweight/obesity training at LOW presented lower EC for a given energy cost of exercise. Our results strongly suggest that NSPA plays a major role in mediating the effects of exercise on energy balance and ultimately on changes in BC. Clinical Trial Registration www.ClinicalTrials.gov, identifier ISRCTN31641049.